Transcriptome sequencing of hybrid bester sturgeon: Responses to poly (I:C) in the context of comparative immunogenomics - Mugue, Nikolai; Terekhanova, Nadezhda; Afanasyev, Sergey; Krasnov, Aleksei (Fish & shellfish immunology, 2019)
Sturgeons represent a substantial scientific interest due to their high economic value, endangered status and also as the most primitive group of ray-finned fishes. Rapid progress in knowledge of sturgeon immunity was achieved recently with use of RNA sequencing. We report transcriptome sequencing of gill, head kidney, and spleen of bester sturgeon (a hybrid of beluga Huso huso and sterlet Acipenser ruthenus) injected with synthetic double-stranded RNA (polyI:C). The composition of transcriptome and responses to treatment were examined in the context of comparative genomics with focus on immune genes. Sturgeon transcripts matched to 21.5 k different proteins (blastx). With reference to Atlantic salmon, the functional groups and pathways of the immune system were uniformly represented: at average 36.5 ± 0.8% genes were found. Immune genes comprise a significant fraction of transcriptome. Among twenty genes with highest transcription levels, five are specialized immune genes and two encode heme and iron binding proteins (serotransferrin and hemopexin) also known as acute phase proteins. Challenge induced multiple functional groups including apoptosis, cell cycle and a number of metabolic pathways. Treatment stimulated innate antiviral immunity, which is well conserved between sturgeon and salmon, the most responsive genes were mx, rsad2 (viperin), interferon induced protein 44 and protein with tetratricopeptide repeats 5, cd87 and receptor transporting protein 3. Results added to knowledge of immune phylogeny. Gain and loss of genes was assessed by comparison with genomes from different phylogenetic groups. Among differentially expressed genes, percentage of acquired and lost genes was much lower in comparison with genes present in all vertebrates. Innate antiviral immunity was subject to the greatest changes in evolution of jawed vertebrates. A significant fraction of genes (15%) was lost in mammals and only half of genes is annotated in public databases as involved in antiviral responses. Change of function may have an important role in evolution of immunity together with gain and loss of genes. •Transcriptome sequencing was performed in sturgeon injected with double-stranded RNA.•The immune transcriptomes of sturgeon and Atlantic salmon are highly similar.•Proactive responses to surrogate infection involved multiple functional groups.•Viral infections activate a large group of orthologs with known or unexplored roles.•Evolution of immunity by genes gain or loss and change of functions is explored.